PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN - Jibu, Taufiq (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research  aims to examine the effect of intellectual capital on firm’s performance. Intellectual capital is measured through VAIC method, which has three components, namely human capital efficiency, structural  capital efficiency and capital employed efficiency. Meanwhile, company's performance is measured using ROE (Return on Equity), Employee Productivity and Tobin's Q. The samples in this research  is determined through random complex in the form of cluster sampling,  resulting  205 companies from all  sectors  listed  in  Indonesia Stock Exchange during the period of 2011-2014. The results of this study demonstrate that human capital efficiency and capital-employed efficiency have positive effects on ROE, Employee productivity, and Tobin's Q. The structural capital efficiency affects Employee Productivity negatively. This result  shows that  companies in Indonesia still relies on physical assets as measured by capital employed efficiency followed by human capital  efficiency in creating added value for the company, which ultimately increase the company’s performance.Keywords: intellectual capital, profitability, productivity, market performance